Assessment of Quality of Life among Parents with Autistic Child - Adyan Lhmood Abd-Alnabi, Kareem Reshak Sachet (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Parents caring for or living with a child diagnosed with a chronic illness such as autism are more likely to experience stress-related issues and have a lower quality of life Aims of the study: assess the quality of life among parents with autistic children. Methodology: A descriptive cross-sectional study conducted by a purposive sample of 120 parents of autistic children were selected through the use of a non-probability sampling approach. The reliability of the questionnaire was achieved through a pilot study and then presented to experts to prove its validity. The total number of items included in the questionnaire was 26-items for quality of life. The data was collected using the self-report method and analyzed by applying a descriptive and inferential statistical data analysis approach. Results: The results of the study indicated that (58.3%) had a poor level of quality of life. And there is a significant association in quality of life with regard to parents’ kinship (p=0 .006), level of education ( p=0.001), social status (p=.050), monthly income (p=0.001), and duration of diagnosis for their children at (p= .011 ). Conclusions : Parents with autistic children presented a poor level of quality of life overall, with a moderate level of quality of life in the physical domain, and in the psychological domain, while the reduced level of quality of life with regard to the social relationship domain, and environment domain. Further study is needed to measure a wide population so that the findings may be generalized.